Dennis Andrews plays Santa for children at the Billy DeFrank Center - Sahl, Ted (photographer):::Creator::::::::::::
Dennis Andrews, "Mr Gay San Jose," wearing a Santa costume entertains three young children at the Billy DeFrank Center. He has his arm around a child on the right, and the male child on the left has his hands close to his mouth and appears to be listening. A young female child can be seen in the background. On the floor are several play school toys, including a truck and a xylophone.